Capture and Maintenance of Balistes capriscus for Aquaculture and Conservation - Mattos, Douglas da Cruz; Cardoso, Leonardo Demier; de Souza, André Batista; Polese, Marcelo Fanttini; de Morais, Tiago Queiroz; Santander-Neto, Jones; Aride, Paulo Henrique Rocha; de Oliveira, Adriano Teixeira; da Silva, Maria Aparecida; Lavander, Henrique David (Fishes, 2025)
The gray triggerfish Balistes capriscus has a wide geographical distribution and is used for commercial and recreational fishing worldwide. In this study, we aimed to provide technical knowledge for developing strategies for the sustainable production of gray triggerfish in aquaculture systems by characterizing the capture procedures for broodstock acquisition and developing a protocol for species maintenance in captivity. Broodstock maintenance data were collected over six months (April to September) each year, whereas breeder data were collected over three months each year (November to January). The number of shipments, capture, and survival of B. capriscus was 100%. The animals grew on average by 9.99 ± 0.11 cm over 9 months and increased their average weight by 1.658 ± 0.1 kg, representing a specific growth rate of 0.62% and an average daily weight gain of 6.14 g/day. The species were fed by alternating the supply of fresh food (minced fish, fish fillets, shrimp, squid, minced octopus and crab), divided into two times, 9:00 a.m. and 4:00 p.m., and offered until the animals were satiated. Regarding the structures used to maintain the breeding stock, 15,000 L tanks are recommended to keep up to 30 breeding individuals.